The gastrointestinal basidiobolomycosis, a rare entity: case report and review of literature - Hashmi, Kanza Huma Zia; Zujajah Hameed; Nadira Mamoon (Journal of the Pakistan Medical Association, 2023)
Gastrointestinal basisdiobolomycosis is a rare fungal infection prevalent in the tropical and subtropical regions. It has variable clinical manifestations that present a challenge for timely diagnosis. Herein, we present a case of gastrointestinal basidiobolomycosis in a 34-year-old male. To the best of our knowledge, it is the first reported case of gastrointestinal basidiobolomycosis from Pakistan. The patient presented with abdominal pain and was first operated for perforated appendix and then for a mesenteric mass based on the findings of CT scan. Histopathologic examination showed broad septate fungal hyphae surrounded by eosinophilic proteinaceous material (Splendore-Hoppeli phenomenon), neutrophils, and histiocytes. Diagnosis of gastrointestinal basidiobolomycosis was established on the basis of this morphology. Keywords: Fungus, Abdominal pain, Basidiobolomycosis.